Evaluating the efficacy of inhaled amikacin as an adjunct to intravenous combination therapy (ceftazidime and amikacin) in pediatric cystic fibrosis pulmonary exacerbation - Rakhshan, Amin; Farahbakhsh, Nazanin; Khanbabaee, Ghamartaj; Tabatabaii, Seyed Ahmad; Sadr, Saeed; Hassanzad, Maryam; Sistanizad, Mohammad; Dastan, Farzaneh; Hajipour, Mahmoud; Bahadori, Amir Reza; Mirrahimi, Bahador (Frontiers in Pharmacology, 2023)
Background: Pseudomonas aeruginosa is the most common microorganism found in the sputum culture of CF patients causing pulmonary destruction. Aminoglycosides have a low diffuse rate from lipid membranes and respiratory system secretions. Due to the burden of pulmonary exacerbation caused by pseudomonas aeruginosa in cystic fibrosis patients in the long term and the limited number of clinical trials focused on appropriate treatment strategies, the present study evaluated the concurrent inhaled and intravenous aminoglycoside antibiotics for pulmonary exacerbation caused by pseudomonas aeruginosa as a safe and effective treatment in children. Method: This study was a blinded, randomized clinical trial phase conducted in a tertiary referral pediatric teaching hospital between May 2021 and May 2022. The patients were randomly allocated to receive intravenously administered ceftazidime and Amikacin alone or with inhaled Amikacin. FEV1, Amikacin through the level, kidney function tests, audiometry, inflammatory markers, hospital stay, and bacterial eradication rate were compared in the two therapy groups. Results: the average FEV1 has increased by 47% in Neb₊group compared to Neb− group following treatment. Hospital stay was lower in Neb₊group. no renal toxicity or ototoxicity was observed in both therapy group. Pseudomonas aeruginosa eradication rate Neb− and Neb₊groups were 44% and 69%, respectively. Conclusion: Concurrent inhaled and intravenous Amikacin is safe and effective in treating Pseudomonas aeruginosa exacerbation in CF patients. Moreover, the co-delivery antibiotics’ route treatment increased the eradication rate. Although not statistically significant, never the less, it is clinically relevant. The intervention reduced the length of hospitalization in this group.